Psychiatric and psychological adverse effects associated with dulaglutide, semaglutide, and liraglutide: A vigibase study - Nishida, Kazuki; Chrétien, Basile; Dolladille, Charles; Ebina, Takumi; Aleksić, Branko; Cabé, Nicolas; Savey, Véronique; Onoue, Takeshi; Yatsuya, Hiroshi (Clinical Nutrition, 2025)
BACKGROUND: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are crucial in managing type 2 diabetes mellitus (T2DM) and obesity. Agents like dulaglutide, semaglutide, and liraglutide mimic endogenous GLP-1, enhancing insulin secretion and promoting satiety. Beyond glycemic control, they offer cardioprotective and neuroprotective benefits. However, concerns about psychiatric adverse effects have emerged, necessitating a systematic assessment of their safety profile. MATERIAL & METHODS: This multinational pharmacovigilance study utilized VigiBase® data up to December 1, 2024, focusing on adverse drug reaction (ADR) reports for GLP-1 RAs. Psychiatric ADRs were classified using MedDRA terminology. Disproportionality analyses were conducted via logistic regression to calculate reporting adjusted Reporting Odds Ratios (aRORs) within reports involving antidiabetic or anti-obesity medications. A causal forest model assessed the individual treatment effect (ITE) of semaglutide on depression and suicidality reporting. RESULTS: Among 2,061,901 reports, 21,414 involved psychiatric ADRs for GLP-1 RAs. Significant signals were observed for anxiety (aROR: 1.26, 95%CI: 1.18-1.35), depressed mood disorders (aROR: 1.70, 95%CI: 1.57-1.84) and suicidality (aROR 1.45, 95%CI: 1.29-1.63) with semaglutide, and eating disorders with all three GLP-1 RAs (aRORs between 4.17 and 6.80). The causal forest model estimated an average treatment effect of 0.0046 for semaglutide on depression and suicidality reporting, with significant heterogeneity across regions and demographic groups. DISCUSSION: The study found no significant increase in overall psychiatric ADR reporting for GLP-1 RAs, except for eating disorders and depression/suicidality in semaglutide-treated patients. Sensitivity analyses before June 4, 2021, found no signals, aligning with RCT data. Post-marketing reports linked semaglutide to depression and suicidal ideation, prompting regulatory investigations. The causal forest model revealed significant heterogeneity in the psychiatric safety profile of semaglutide, with regional factors influencing ADR reporting. CONCLUSION: While GLP-1 RAs do not show a significant increase in overall psychiatric ADR reporting, findings suggest that clinicians should remain vigilant for potential depressive symptoms and suicidality, particularly in individuals with obesity treated with semaglutide since its approval for weight management.